Setting up child health and mortality prevention surveillance in Ethiopia [version 2; peer review: 2 approved, 1 approved with reservations] - Anna C. Seale; Lola Madrid; Nega Assefa; Hanan Abdurahman; Stefanie Wittmann; Letta Gedefa; Nardos Teferi; Natnael Debela; Alexander Mohamed; Tigistu Samuel; Tseyon Tesfaye; Hiwot Yigzaw; et al. (Gates Open Research, 2022)
Background: Mortality rates for children under five years of age, and stillbirth risks, remain high in parts of sub-Saharan Africa and South Asia. The Child Health and Mortality Prevention Surveillance (CHAMPS) network aims to ascertain causes of child death in high child mortality settings (>50 deaths/1000 live-births). We aimed to develop a “greenfield” site for CHAMPS, based in Harar and Kersa, in Eastern Ethiopia. This very high mortality setting (>100 deaths/1000 live-births in Kersa) had limited previous surveillance capacity, weak infrastructure and political instability. Here we describe site development, from conception in 2015 to the end of the first year of recruitment. Methods: We formed a collaboration between Haramaya University and the London School of Hygiene & Tropical Medicine and engaged community, national and international partners to support a new CHAMPS programme. We developed laboratory infrastructure and recruited and trained staff. We established project specific procedures to implement CHAMPS network protocols including; death notifications, clinical and demographic data collection, post-mortem minimally invasive tissue sampling, microbiology and pathology testing, and verbal autopsy. We convened an expert local panel to determine cause-of-death. In partnership with the Ethiopian Public Health Institute we developed strategies to improve child and maternal health. Results: Despite considerable challenge, with financial support, personal commitment, and effective partnership, we successfully initiated CHAMPS. One year into recruitment (February 2020), we had received 1173 unique death notifications, investigated 59/99 MITS-eligible cases within the demographic surveillance site, and assigned an underlying and immediate cause of death to 53 children. Conclusions: The most valuable data for global health policy are from high-mortality settings, but initiating CHAMPS has required considerable resource. To further leverage this investment, we need strong, sustained, local research leadership, and to broaden the scientific remit. To support this, we have set up a new collaboration, the “Hararghe Health Research Partnership”.